Geração de layout de interfaces gráficas baseado em ontologias para documentos do Registro Eletrônico em Saúde - Bezerra, Andrea Fernanda Fontes (2014)
Health informatics is a domain that presents several challenges to be overcome. Electronic Health Records (EHR) are one of its most important subdomain, in charge of storage, exhibition, and manipulation of patient clinical information, among others. EHR systems require domain flexibility, which allows modifications in the structure of documents without application recompilation or redeployment, for instance, in a web server. Current approaches in the literature propose generic models to represent domain and presentation, without ontological definitions for user interface (UI) layout and style. These, when properly organized, improve the acceptance of the system by users. This work aims to develop a framework to layout and style generation for graphical user interface of EHR documents, based on Web Ontology Language (OWL) ontologies and using restrictions. By centralizing and combining metadata from biomedical and documents domains, it was possible to apply layout and style to EHR documents, with the use of grids, including additional ontological definition of presentation formats for the medical field, facilitating UI development and maintenance.